PUBLIC OWNERSHIP IN THE LEGAL SYSTEM OF THE REPUBLIC OF CROATIA - Mario Jelušić (Zbornik Radova Pravnog Fakulteta u Splitu, 2009)
As opposed to civil law, the theory of administrative law comprehends the concept of public good as a good (thing) which, on the one hand, is in general use, and which everyone can use according to the principle of equality. Therein no one may impede or stop someone else from using that good as long as it is being used in its usual way according to its nature. Furthermore, a public good has the characteristic that it is exempt from civil law transaction. The theory of civil law in Croatia calls these things items of interest to the Republic of Croatia, relying on the formulations from article 52 of the Croatian Constitution. In the theory of administrative law, the division of public goods was practised taking into account the object, how it was created, its purpose, and the criterion of ownership (whether or not it can be the subject of civil legal ownership). In this sense land, water, maritime, and air goods are differentiated. Public goods are also divided according to how they came about, (public goods created naturally and by human action). Furthermore public goods are divided according to the criteria of their creation, of their purpose and of ownership. A further question which arises is the administration of public goods. The state, units of local government (regional), public institutions (museums, archives, libraries) and special public companies have the right such goods. The author also analyses the question of when these goods were declared existent as public goods and when they ceased to be public goods as in those cases where by its very nature of a being public good this is not superfluous as in the case of air or maritime goods. Examples of certain Croatian laws which regulate certain types of public goods are given. The question of demarcating public goods and their use also represents an important area in regulating public goods. Disputes related to public goods may arise due to the way they are used. This can be seen in the example of the question of whether a certain good can be classified as public. The government administration is certainly authorised to reach such decisions and the court can be given the authority to decide on certain disputes which arise related to the use and administration of public goods. In addition, the author deals with the issues of the authority over, keeping records of, and the protection of public goods.